2010
DOI: 10.1021/ic100878s
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Influence on Metal Aggregation: a Unique Bonding Mode for Pyridylpyrrolides

Abstract: The synthesis and characterization of a Cu(I) complex with a cis-bidentate monoanionic nitrogenous ligand, 2-pyridylpyrrolide, L, is reported. This shows binding of one base B = MeCN or CO per copper in a species LCu(B), but this readily releases the volatile ligand under vacuum with aggregation of transient LCu to a mixture of two enantiomers of a chiral trimer: a zwitterion containing inequivalent Cu(I) centers, possible via a new bonding mode of pyridylpyrrolide, and one with nitrogen lone pairs donating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…We confirmed that we have synthesized the same HL 1 as obtained earlier, by identity of the NMR chemical shifts. We have also reported the crystal structure of HL 1 itself, showing this same, corrected connectivity (Scheme ).…”
Section: Methodsmentioning
confidence: 52%
“…We confirmed that we have synthesized the same HL 1 as obtained earlier, by identity of the NMR chemical shifts. We have also reported the crystal structure of HL 1 itself, showing this same, corrected connectivity (Scheme ).…”
Section: Methodsmentioning
confidence: 52%
“…Consequently, trans-2 was chemically reduced to [2] − by cobaltocene (E 1/2 = −1.33 V vs FcH/[FcH] + ) 50 giving the diamagnetic cobaltocenium cuprate [CoCp 2 ][2] (Scheme 1) which was characterized by NMR, IR, and UV−vis spectroscopy as well as by mass spectrometry and elemental analysis (Experimental Section and Supporting Information, Figures S7−S10). The related cuprate K[CuL 1 2 ] with pyridylpyrrolido ligands [L 1 ] − has been prepared from Cu 3 L 1 3 39 and potassium and characterized by NMR spectroscopy and mass spectrometry. 51 A less than four-coordinate structure has been suggested for K[CuL 1 2 ].…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This core structure is quite similar to those of Ag 3 N-heterocyclic carbene complexes, [Ag 3 (CH 3 im(CH 2 py)) 3 -(NCCH 3 ) 2 ] 3− , [Ag 3 (im(CH 2 py) 2 ) 3 ] 3− and [Ag 3 (im(CH 2 Mepy) 2 ) 3 ] 3− , 22,23 and Cu 3 monopyridylpyrrole complex. 24,25 Short Ag-Ag distances in 1 (Ag1-Ag2 2.9370(12) Å, Ag1-Ag3 2.8732(13) Å, Ag2-Ag3 2.8937(13) Å) due to the silver-silver interaction are slightly longer than av. 2.784 Å observed in Ag 3 N-heterocyclic carbene complexes.…”
Section: Description Of Structurementioning
confidence: 99%